Business Development Services and Government Regulations: Prospects and Challenges of Youth-Owned Enterprises in Kigali Rwanda - Samuel Hakizimana; Stephen Muathe Makau; Lucy Kavinda (International Journal of Business and Social Science Research, 2023)
Small and medium-sized businesses are crucial for creating jobs and reducing poverty, and Rwanda's economic growth. Business development services as a central component of government and non-government initiatives to expand occupation, provide greater income, and give economic stability. However, small and medium enterprises in Rwanda are experiencing poor performance since there was a reduction in SMEs Output from 58% in 2020 to 30% in 2021. Those obstacles can be improved by adopting business development services as an approach. Therefore, the focus of this paper was to examine how business development services affect the performance of youth-owned small and medium enterprises in Kigali City, Rwanda. The Resource-Based View, the Theory of Stage of Development, and Schumpeter’s Theory of Innovation were the main theories. This study used positivism as a research philosophy. An explanatory research design was employed on a sample size of 154 small and medium enterprises selected from the target population of 256 small and medium enterprises in Kigali, Rwanda. The study recommends policy and practice ramifications that can be used to improve business development services on the performance of youth-owned businesses in Rwanda. The study recommends the management of youth-owned enterprises strengthen their networking services, financial services, training services, and marketing services so that small and medium enterprises will be able to learn more and gain vital business potential which will enable them to better manage their businesses and enhance their long-term profitability and performance. Furthermore, the findings also established that government regulations in Rwanda significantly moderate the relationship between business development services and the performance of the business in Kigali city. In particular, the government should review taxes charged by the running of the enterprise and the process of obtaining a license to participate in the business. This will make it possible for young business owners to understand and take advantage of numerous business development services, which will ultimately improve their business performance.